(untitled) (Interdisciplinary Studies Journal, 2024)
This research aimed to analyze the digital technologies used by mathematics teachers during remote teaching during the COVID-19 pandemic, describing the activities developed and exposing the potential and limitations of these technologies. The study consisted of a qualitative-quantitative approach of a descriptive and exploratory nature. As a data collection instrument, an online questionnaire was used, consisting of ten questions that were answered by 34 mathematics teachers from municipal, state and private schools in the city of Petrolina - PE. The questions dealt with the technological tools used, guidance or training for the use of these tools and the intention to continue using digital technologies after the pandemic. According to the teachers, activities on digital platforms were diverse and comprehensive, with the use of various tools such as WhatsApp, Google Classroom, Google Meet, Google Forms, YouTube, Instagram, Canva and Padlet. The main capabilities of these tools were agile communication with students and provision of study materials. However, limitations were also identified such as lack of access to devices and internet, fatigue due to excessive time in front of screens, difficulty maintaining attention in online classes and adapting to new technologies.